Soil salinization in marshes. Study case: Samborombón Bay wetland, Argentina - Carol, Eleonora S.; Kruse, Eduardo E.; Cellone, Francisco A. (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2015)
The southern sector of the Samborombón Bay (Buenos Aires, Argentina) is an extensive marsh that is associated with an intertidal wetland environment. Different engineering works were built to avoid tidal inflow and to increase the livestock grazing areas. The objective of this work is to assess if the regulation of tidal inflow causes a chloride content change in the surface sediments, affecting the soil salinity of the wetland. Interpretation of satellite images, field surveys, sampling of sediments, and electrical conductivity and levels measurements of surface and groundwater were carried out. The results allowed us to recognize how engineering works (embankments and internal roads) alter the natural hydrological behavior, and, therefore the chloride content in the sediment. Soil salinization problems are recognized in areas where the tidal water accumulates and then evaporates forming halite precipitates. Future engineering works should be planned so as to minimize the alteration of the water flow in order to achieve a sustainable management of natural resources in the wetland.